Issues on the Role of Formal Requirements for Validity of Immovable Transactions in Ethiopia: the Case of Amhara Region - Moges, Melkamu Belachew; Agegnehu, Alelegn W (Bahir Dar University Journal of Law, 2022)
This article deals with the question of formal requirements and their relevance to the validity of transactions relating to immovable properties both in urban and rural settings. The article discovers that while some rules try to mention the types of formal requirements and their effect on the validity of legal transactions on immovable properties, there is still a problem of lack of coherence within each of the legislations as well as among the various legislations. Similarly, there are divergent interpretations of these rules. One cause, we argue, is the failure to demarcate the distinction among multiple existing formal requirements. In particular, legal professionals have been confused with the difference between authentication and registration requirements. This research aims to supplement the current discourse on the issue by critically identifying the different formal requirements described in various laws, both the long existing Civil Code and the relatively recent urban and rural land use and administration legislations, and advancing more comprehensive arguments on the issue. To do so, it provides a theoretical definition of the relevant concepts based on international standards and links these definitions to the definitions given under our law. In addition, it analyses a few sample court cases decided by the Amhara region Supreme Court as well as offering supplementary information from a few key informants and a focus group discussion.